Cold Storage Solutions to Reduce Post-Harvest Loss: Start-ups for Youth in the Agricultural Supply Chain - Mohammed Sadiq, Sanusi; Paul Singh, Invinder; Ahmad, Muhammad Makarfi; Sanyinna Sani, Bashir (New Countryside, 2025)
Post-harvest losses represent a major challenge to global food systems, accounting for up to 30–50% of agricultural output losses, particularly in perishable crops such as fruits, vegetables, dairy, and fish. These losses significantly impact food security, farmer incomes, and national economies—most acutely in developing countries where infrastructure is limited. Cold storage technologies have emerged as one of the most effective solutions to address this issue by preserving the quality and shelf life of perishable produce. In recent years, agritech start-ups, driven by innovative youth entrepreneurs, have been at the forefront of deploying scalable and affordable cold storage solutions, ranging from solar-powered cooling units to mobile refrigeration systems and decentralized storage networks. This communication critically examines the dynamic intersection of cold storage innovations, youth entrepreneurship, and agricultural value chains. It explores the relevance of key theoretical models such as innovation diffusion theory, sustainable livelihoods framework, and supply chain integration theory to understand the adoption and impact of cold storage technologies. Through case studies and evidence from sub-Saharan Africa and South Asia, we highlight how youth-led start-ups are leveraging technology, financing, and digital platforms to bridge critical gaps in agri-logistics. Despite these promising developments, challenges persist, including high capital costs, inconsistent energy supply, inadequate technical skills, and weak policy support. As such, this study explores enabling policy frameworks, investment opportunities, and capacity-building strategies necessary for the sustainable deployment of cold storage solutions. Emphasis is placed on the transformative potential of youth-driven innovations in shaping resilient, inclusive, and climate-smart agri-food systems.